2014
DOI: 10.1177/0894845314555124
|View full text |Cite
|
Sign up to set email alerts
|

What Young Adolescents Think About Engineering

Abstract: To explore young adolescents' interest in engineering as a future career, we examined the influence of gender and grade level on participants' (N ¼ 197, aged 10-13) views of engineering. One group (107 students) viewed a brief engineering video and wrote why they felt the same or different about engineering following the video. Qualitative analyses revealed that some reported viewing engineering differently and more positively, although most did not want to be an engineer. Girls, more than boys, noted that eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…They generally exhibit less interest or a more negative attitude toward technology compared to boys. It was reported that girls were less interested in and had lower ambitions than boys regarding technology (Chang et al, 2009;Jennings et al, 2015;Shoffner et al, 2015;Villas-Boas, 2010). Several studies (Ardies et al, 2015;Master & Meltzoff, 2016;Rasinen et al, 2009) indicated that girls typically express interest in certain technological subjects around the age of 10; however, their interest tends to decline after that.…”
Section: Results; Study Imentioning
confidence: 99%
“…They generally exhibit less interest or a more negative attitude toward technology compared to boys. It was reported that girls were less interested in and had lower ambitions than boys regarding technology (Chang et al, 2009;Jennings et al, 2015;Shoffner et al, 2015;Villas-Boas, 2010). Several studies (Ardies et al, 2015;Master & Meltzoff, 2016;Rasinen et al, 2009) indicated that girls typically express interest in certain technological subjects around the age of 10; however, their interest tends to decline after that.…”
Section: Results; Study Imentioning
confidence: 99%
“…A young person will not choose to pursue a STEM career if they are not aware of the career possibilities in those fields, they do not know anyone who works in STEM, or they do not understand what professionals in those careers do [5], [6]. Furthermore, many K-12 students have few to no experiences with engineering, which could partially explain why there are not more students pursuing engineering degrees [7].…”
Section: Introductionmentioning
confidence: 99%